Radiotherapy has a survival advantage over surgery in patients with choroidal melanoma: a retrospective cohort study of 6,871 patients - Wu, Yifan; Shi, Lu; Ye, Zhiqiang; Zhou, Yi; Wang, Feiran; Zhang, Yulan (Frontiers in Surgery, 2025)
BackgroundChoroidal melanoma is a rare yet aggressive ocular malignancy, accounting for approximately 85% of all ocular melanomas. This study aimed to investigate the association between treatment modalities and the risk of all-cause mortality and choroidal melanoma-specific mortality, thereby comparing the effects of different treatment modalities on patient prognosis.MethodsData from patients diagnosed with choroidal melanoma between 2004 and 2021 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. A total of 6,871 cases were included in the analysis. Univariate analysis, stratified analysis, and multiple regression analysis were performed to evaluate all-cause mortality and choroidal melanoma-specific mortality across different treatment modalities. Survival curves for the overall and stratified populations were generated using the Kaplan–Meier method. Choroidal melanoma-specific mortality was estimated using the competing risk regression method of Fine and Gray.ResultsIn the fully adjusted model, the radiotherapy-only group exhibited a 45% reduction in all-cause mortality (HR = 0.55, 95% CI = 0.50–0.60, p < 0.0001) and a 54% reduction in choroidal melanoma-specific mortality (HR = 0.46, 95% CI = 0.41–0.52, p < 0.0001) compared to the surgery-only group. The radiotherapy group demonstrated superior long-term survival outcomes compared to other treatment modalities, with the highest 5-year overall survival (OS) rate of 0.7769 (95% CI = 0.7651–0.7889) and 10-year OS rate of 0.6203 (95% CI = 0.6038–0.6372). Additionally, the radiotherapy group achieved the highest 5-year choroidal melanoma-specific survival (CSS) rate of 0.8615 (95% CI = 0.8514–0.8717) and 10-year CSS rate of 0.7715 (95% CI = 0.7567–0.7866).ConclusionsAmong patients diagnosed with choroidal melanoma, those who underwent radiotherapy alone exhibited significantly higher overall survival (OS) and choroidal melanoma-specific survival rates compared to those who received surgical intervention alone. However, for patients with advanced disease or evidence of metastatic spread, the individualization of treatment regimens remains critically important.